(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article analyzes the semantic characteristics of praise and condemnation verbs in Abdurahmon Jami’s "Al-Favoidu-z-Ziyoiyya", their grammatical forms, and usage contexts. Additionally, it examines the role and significance of these verbs in Arabic grammar.